Advanced Techniques for Storage Optimization in Resource-Constrained Systems Using AI and Machine Learning - Subhan Baba Mohammed; Bhavani Krothapalli; Chandrashekar Althat (Journal of Science & Technology, 2023)
The ever-increasing volume and complexity of data pose significant challenges for storage management in resource-constrained systems. These systems, often characterized by limited processing power, memory capacity, and energy availability, are prevalent in various domains including Internet-of-Things (IoT) devices, edge computing platforms, and mobile computing environments. Traditional storage management techniques are often inadequate in such scenarios, leading to inefficient resource utilization, performance bottlenecks, and limited data accessibility. This paper delves into advanced techniques that leverage Artificial Intelligence (AI) and Machine Learning (ML) to optimize storage in resource-constrained systems. Our focus is on enhancing storage efficiency and system performance while operating within the limitations of these resource-scarce environments. The paper commences by outlining the fundamental challenges associated with storage management in resource-constrained systems. We discuss the limitations in terms of storage capacity, processing power, and energy consumption. We further explore the impact of these limitations on factors like data access latency, retrieval throughput, and overall system responsiveness. Subsequently, we delve into established storage management techniques employed in these systems. These techniques include data compression algorithms, caching strategies, and data prefetching methods. While effective to an extent, these traditional techniques often lack the adaptability and dynamic decision-making capabilities required to optimize storage under constantly evolving data access patterns and system resource fluctuations. To address these limitations, the paper explores the integration of AI and ML into storage management frameworks for resource-constrained systems. We posit that AI, with its ability to learn and adapt, offers a promising avenue for optimizing storage utilization and enhancing system performance. The paper delves into specific AI and ML techniques applicable to storage optimization in this context. One prominent technique explored is the application of machine learning for data compression. We discuss how ML algorithms can be trained on specific data types and access patterns to dynamically select the most effective compression techniques. This approach can significantly improve compression ratios while minimizing computational overhead, a critical factor in resource-constrained environments. Another key technique explored is the utilization of machine learning for intelligent caching. Traditional caching strategies often rely on static rules or heuristics to determine which data to cache. However, these strategies may not adapt well to dynamic access patterns. Machine learning algorithms can be employed to analyze past access patterns and predict future data requests. By proactively caching frequently accessed data, ML-driven caching can significantly reduce access latency and improve system responsiveness. Furthermore, the paper explores the potential of data prefetching techniques enhanced by machine learning. Data prefetching involves anticipating future data needs and retrieving them before they are explicitly requested. Traditional prefetching methods often rely on simple heuristics or predefined access patterns. ML algorithms can be trained to analyze historical access patterns and user behavior to make more accurate predictions about future data needs. This intelligent prefetching can significantly improve data availability and reduce retrieval delays. Additionally, the paper investigates the role of predictive analytics in storage optimization. By analyzing historical access patterns and system resource constraints, predictive models can anticipate storage bottlenecks and resource limitations. This enables proactive storage management strategies, such as data migration or load balancing across available storage resources. Predictive analytics, powered by machine learning, can help prevent system performance degradation and ensure efficient storage utilization. Finally, the paper explores the potential of reinforcement learning for storage optimization in resource-constrained systems. Reinforcement learning allows an ML agent to learn through trial and error by interacting with the storage environment. The agent receives rewards for making storage decisions that optimize resource utilization and performance. Through continuous learning and adaptation, reinforcement learning can develop robust storage management strategies that are highly effective in dynamic and unpredictable environments. This paper critically evaluates the potential and limitations of each AI and ML technique for storage optimization in resource-constrained systems. We discuss the trade-offs between performance gains, resource consumption by the AI/ML models themselves, and the overall impact on system efficiency. Furthermore, we address the challenges associated with implementing these techniques, such as limited training data availability on resource-constrained devices and the need for efficient and lightweight AI/ML models to minimize computational overhead. The paper concludes by outlining promising directions for future research in this domain, including exploring federated learning approaches for distributed storage management and investigating the application of deep learning techniques for even more sophisticated storage optimization strategies.